2016
DOI: 10.5430/ijhe.v6n1p101
|View full text |Cite
|
Sign up to set email alerts
|

Creating Enabling Environment for Student Engagement: Faculty Practices of Critical Thinking

Abstract: Critical thinking (CT) is considered an important attribute in practice disciplines and faculty members in nursing, medicine, and education are expected to facilitate the development of CT in their graduates so that these individuals can be critical, reflective, competent, and caring professionals and service providers. When students are actively engaged in their learning, and classrooms have an enabling environment, CT is promoted. Teachers must reflect upon their pedagogy when students do not participate in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Disengaged students also do not display the critical thinking skills necessary for creating occupation-based interventions or stimulating learning. Cassum et al (2017) suggested that when educators provide active learning opportunities in the classroom, the activities should foster communication, student engagement, creativity, self-directedness, and critical thinking The experiences of students in both courses indicated that student engagement and participation were positively impacted using this hybrid curriculum model. The active learning strategies the flipped classroom, peer instruction and classroom discussion were important to the success of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Disengaged students also do not display the critical thinking skills necessary for creating occupation-based interventions or stimulating learning. Cassum et al (2017) suggested that when educators provide active learning opportunities in the classroom, the activities should foster communication, student engagement, creativity, self-directedness, and critical thinking The experiences of students in both courses indicated that student engagement and participation were positively impacted using this hybrid curriculum model. The active learning strategies the flipped classroom, peer instruction and classroom discussion were important to the success of the model.…”
Section: Discussionmentioning
confidence: 99%
“…Critical thinking improves when students are engaged with active teaching and learning strategies. 17 However, despite of the research supporting that the benefits of utilizing different teaching learning strategies, nursing teachers are still utilizing traditional teaching learning strategies. 18 Parenting role is considered important for the cognitive and behavioral development of the student.…”
Section: Discussionmentioning
confidence: 99%
“…Thirty-three between ages 15-20 years are found in progressive creativity CTD level. Female students are more at the progressive creativity CTD scores (37) as compared to male students (17). The majority of the students with matric from public sector school and FSc from private sector school are at progressive level of creativity CTD.…”
Section: Creativitymentioning
confidence: 99%
“…An effective seating arrangement must, however, facilitate learners according to the teaching-learning methodology in use, such as collaborative learning, lecture style, group work, etc. (Cassum & Gul., 2017). The technologically advanced, modern classroom of today demands that the physical arrangements of the classroom align with teaching-learning tools and equipment.…”
Section: Physical Management Of the Classroommentioning
confidence: 99%